BASICS OF CONSERVATIVE TREATMENT OF PRIMARY OPENANGLE GLAUCOMA - Sabirova Dilrabo Bahodirovna; Kadirova Aziza Muratovna (Scholar Express Journals, 2024)
We observed 47 patients, of which 31 were women, 16 were men, aged from 41 to 63 years. All patients were divided into 3 groups. Group 1 included 20 patients (40 eyes) in whom the anterior chamber angle (ACA) was open (3-4 degree of opening), subatrophy of the iris root was expressed, destruction of fibrous structures, and a network of blood vessels was visible. In 16 patients (31 eyes), who were assigned to group II, the following were revealed: the UPC is open (3-4 degrees of opening), moderate exo and endopigmentation, exfoliation in some patients on the trabecula. Group III included 11 patients (22 eyes), in whom examination revealed an open, but narrow, coracoid angle of the anterior chamber, uneven pigmentation of the structures of the APC, and destruction of fibrous structures. . Based on the results of our observations, we can conclude that, based on gonioscopy data, a patient with open-angle glaucoma in the initial stage of the disease can be immediately prescribed a type of treatment in the form of monotherapy or a combination of drugs and determine its prognosis.
Keywords: open-angle glaucoma; gonioscopy; the angle of the anterior chamber; intraocular pressure